ANALISIS PERAN PEREMPUAN DALAM MENUNJANG PENDAPATAN KELUARGA PADA KERAJINAN RAJUTAN - Diani, Ni Kadek Fitri; Aswitari, Luh Putu (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol 9 No 3 (2020): Vol. 9, No.3, Maret 2020, pp (473-718), 2020)
The purpose of this study was to analyze the role of women in supporting family income in knitwear. This research was conducted in Pujungan Village, Pupuan Subdistrict, Tabanan Regency. The analysis technique used in this study was Moderation Regression Analysis. The results of this study are that outpouring of working time does not have a positive effect on the contribution of female workers in knitting in Pujungan Village, Pupuan District, Tabanan Regency. on the contribution of female workers to knitted handicrafts in Pujungan Village, Pupuan District, Tabanan Regency, work experience does not have a positive effect on the contribution of female workers to knit crafts in Pujungan Village, Pupuan District, Tabanan Regency. knitted crafts in Pujungan Village, Pupuan District, Tabanan Regency